Randomized phase 2 trial of erlotinib in combination with high‐dose celecoxib or placebo in patients with advanced non‐small cell lung cancer. Issue 18 (29th May 2015) - Reckamp, Karen L.; Koczywas, Marianna; Cristea, Mihaela C.; Dowell, Jonathan E.; Wang, He‐Jing; Gardner, Brian K.; Milne, Ginger L.; Figlin, Robert A.; Fishbein, Michael C.; Elashoff, Robert M.; Dubinett, Steven M.
<x xml:space="preserve">Abstract</x> BACKGROUND Cyclooxygenase 2 (COX‐2)‐dependent signaling represents a potential mechanism of resistance to therapy with epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors. This is mediated in part through an EGFR‐independent activation of mitogen‐activated protein kinase (MAPK)/extracellular signal‐regulated kinase (Erk) by prostaglandin E2 (PGE2). PGE2 promotes downregulation of E cadherin and epithelial to mesenchymal transition. The current study investigated EGFR and COX‐2 inhibition in patients with non‐small cell lung cancer (NSCLC) and elevated baseline urinary metabolite of PGE2 (PGEM). METHODS Patients with stage IIIB/IV (AJCC 6th edition) NSCLC who progressed after at least 1 line of therapy or refused standard chemotherapy were randomized to receive erlotinib and celecoxib versus erlotinib and placebo. The primary endpoint was progression‐free survival (PFS) with 80% power to detect a 50% improvement with a 1‐sided significance level of .2 in the intent‐to‐treat and elevated baseline PGEM populations. Secondary endpoints included response rate, overall survival, and evaluation of molecular markers to assess targeting COX‐2–related pathways and evaluate EGFR tyrosine kinase inhibitor resistance. RESULTS A total of 107 patients were enrolled with comparable baseline characteristics. Among the patients treated with celecoxib, those with wild‐type EGFR were found to have an increased PFS (3.2 months vs 1.8 months; P = .03). PFS was numerically improved among patients in the intent‐to‐treat group who received erlotinib and celecoxib compared with those treated with erlotinib and placebo (5.4 months vs 3.5 months; P = .33) and was increased in patients in the erlotinib and celecoxib arm with elevated baseline PGEM (5.4 months vs 2.2 months; P = .15). Adverse events were similar in both treatment arms. CONCLUSIONS The combination of erlotinib and celecoxib did not appear to improve outcomes in an unselected population, but selection by elevated baseline PGEM led to an increase in PFS with this combination. Patients with EGFR wild‐type status may benefit from the combination of erlotinib and celecoxib. Cancer 2015;121:3298–3306. © 2015 American Cancer Society.